Impact of vegetative emissions on urban ozone and biogenic secondary organic aerosol: Box model study for Berlin, Germany. (1st March 2018) - Bonn, Boris; von Schneidemesser, Erika; Butler, Tim; Churkina, Galina; Ehlers, Christian; Grote, Rüdiger; Klemp, Dieter; Nothard, Rainer; Schäfer, Klaus; von Stülpnagel, Albrecht; Kerschbaumer, Andreas; Yousefpour, Rasoul; et al.
Abstract: Tropospheric ozone and particulate matter affect human health and cause vegetation stress, dysfunction and damages. In this study we investigate the effect of increasing urban vegetation i.e. tree species on atmospheric chemistry, a potential urban management strategy to counteract high levels of local pollutants such as ozone, OH and PM10 caused by e.g. traffic. We use an extended version of an atmospheric chemistry box model including detailed gas-phase chemistry, mixing layer height variation and secondary organic aerosol calculations based on observations for Berlin, Germany. It is shown to accurately simulate the observed ozone volume mixing ratios during the intensive measurement period in July 2014 (BAERLIN2014) if basic parameters such as nitrogen oxides, meteorological conditions, PM10 concentrations as well as volatile organic compounds (VOCs) are considered as 1 h resolved datasets. Based on this setup the effects of changing present day vegetation mixture by 24 different relevant tree species and of urban greening is tested to elucidate benefits and drawbacks in order to support future urban planning. While the present day vegetation causes boundary layer ozone to decline slightly at 35 °C, individual tree types alter the ozone production rate and concentration as well as the secondary organic aerosol mass in different ways. Our results suggest that trees intensively emitting isoprene such as black locust, European oak and poplar result in higher ozone and total PM10 concentrations than at present, while tree species emitting primarily monoterpenes such as beech, magnolia and wayfaring trees yield less of both. This is in line with the similar behaviour of OH concentration and new particle formation rates. Thus, for future urban planning including urban greening, consideration of the beneficial and harmful aspects of tree species need to ensure that citizens benefit from and are not being negatively affected by climate adaptation strategies.